Membangun Reputasi Perusahaan untuk Menjaga Loyalitas Nasabah (Studi Kasus: Panin Dubai Syariah Bank) - Purnamasari, Oktaviana; Hamudya, Topan Perkasa (School of Communication - Atma Jaya Catholic University of Indonesia, 2022)
The intense competition in the banking world in maintaining reputation-based customer loyalty is very interesting to study. In relation to the Islamic banking industry, efforts to maintain loyalty are carried out in various ways. This research is different from previous research in the context of Islamic banks in that there is an emotional-religious customer segment that has a higher emotional attachment to the reputation of Islamic banks, which creates loyalty. The purpose of this study is to examine how PDSB builds a company's reputation to maintain customer loyalty. This research uses a case study method through a qualitative approach and is descriptive in nature. The results found in this study are that PDSB continuously builds and strengthens the company's reputation covering aspects of Vision and Leadership through the ability to see market opportunities, have strong and excellent leadership, and have a clear vision of what to aim for in the future, Social Responsibility that is realized in the form of social responsibility activities towards social and environmental development, Financial Performance by achieving financial performance achievements, Workplace Environment by creating a good and conducive organizational climate through increasing employee engagement, Product and Services through product innovations and services that have process speed and flexibility while maintaining quality and compliance aspects, as well as Emotional Appeals to maintain customer loyalty.